The relationship between psychological distress with salivary á-amylase and physical symptoms among breast cancer survivors - Yong, H. W.; Hashim, Zailina; Jamil @ Osman , Zubaidah; Moin, Saidi; Yong, H. Y.; Mohd Shariff, Zalilah (Scientific Research Publishing, 2013)
Background and Aims: This study examined the stress levels, the stressors and biomarker such as Alpha (α)-Amylase enzyme which is secreted under distress conditions. The aim was to determine the relationship between these three variables.